(untitled) (Journal of history, 2019)
The article describes about Askanbek Allanazarov studied 33 years of Polish and Japanese prisoners of war in the SECOND world war. Conveys a sense of the structure and content of the personal Fund of A. Allanazarov. Defined approaches to the study of personal documents of archival Fund. A brief biography of the officer-teacher is shown. The search for 133 Kazakh wars buried in Poland during the II world war will be justified. It is considered issledovaniia of Aslanbeka of Saparovich in search of a member of the guerrilla movement named «Zhezkazgan» or «Ivanovich from Kazakhstan». Refers to the study of the documents of the Polish archives of Kazakh named Sasha, i.e. Oxikbai Kasymbekov. Describes the participation of Aslanbeka of Saparovich fate deformirovanii Polish girls Nata Bogdanovich and became her mother Dorie Bass. Characterised by awards of the Polish state awarded to A. Allanazarova. The article analyzes the search for a research officer based on archival documents in the post-Soviet period 41 burial grounds of Japanese prisoners of war in Kazakhstan and the definition of the names of 58,900 dead soldiers. The award is shown. Allanazarova the order of the Rising sun gold rays and rosettes.